The Bacterial Disinfection of Water Using a Galloping Piezoelectric Wind Energy Harvester - Poudel P.; Sharma S.; Ansari M.N.M.; Kumar P.; Ibrahim S.M.; Vaish R.; Kumar R.; Thomas P. (MDPI, 2023)
Copper oxides; Disinfection; Electric potential; Energy harvesting; Nanowires; Piezoelectricity; Potable water; Water treatment; Bacterial disinfection; Copper oxide nanowire (CuONW); Copper oxide nanowires; Electric field treatment; Electroporation; Energy Harvester; Galloping; Locally enhanced electric field treatment; Piezoelectric; Piezoelectric energy harvesting; Wind power